(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Accidents are the cause of death and disability for millions of children every year. Objectives: To study safety practices in a group of Iraqi parents, and its association with some demographic factors. Methods: A total of 360 parents of children aged 1-6 years were interviewed using a questionnaire form designed by the authors. Results: Majority (80%) of families keep medications in unsafe places, in addition to that 52.3%, 6.2% and 76.6% of parents keep antiseptics, kerosene and match boxes in unsafe places respectively. There was a significant association between keeping antiseptics in safe places with educational level of both parents and type of home (p<0.05). Higher rates of road-traffic accidents were reported among families who allow their children to play with bicycle in the street (15.6%) or play unsupervised in the street (16%) than those families who don’t (7.4% and 3.6% respectively). More road traffic-accidents were detected within families with more number of children. Poisoning histories were detected more within extended (17%) than nuclear families (6.5%), and more among children whom mothers don’t work outside home than children with working mothers (12.3% vs. 2.9%). Conclusion: Child safety mal practices are still common among our parents. Key words: Child safety, Poisoning, Child injuries Iraqi J Med Sci, 2004; Vol. 3 (1): 89-92